KOORDINASI PENGATURAN RAMBU-RAMBU LALU LINTAS DI KABUPATEN SIAK - Siti Muanisah; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Traffic and road transport is part of the national transportation system must be developed to realize the potential and role of security, safety, order and the smooth traffic and road transport in order to support economic development and regional development. Transportation system must be in order and continuously refined to ensure the mobility of people and goods in order to ensure the welfare of society. Therefore to realize the implementation of traffic and road transport that is safe, safe, orderly, and well, need the support of the network and the availability of support facilities and transport traffic and good road worthy. As the result of the author’s observation on the field are still many roads that the country siak not equipped with traffic signs in conformity with the needs and placement of signs that do not consider the condition of the road, the placement of signs that do not consider the condition of the road will cause hazardous conditions for the road users. Problem is this research is how to coordinate the setting of traffic signs in siak district and what are the factors that affect the coordination arrangement of traffic signs in siak district. As for the purpose of this research is to investigate the coordination arrangement of traffic signs and to determine the factors that influence the coordination arrangement of traffic signs.The concept of the theory is that researchers use is the organization, coordination, traffic signs, and traffic. This study uses qualitative research methods to study descriptive data. In data collection, the researcher used interview techniques, observation and study of literature. Using key informans as a source of information.The results of this study indicate that the coordination arrangements of traffic signs in siak district has not been efektive, it can be seen from the lack of traffic signs in siak district roads and there are many signs that the placement is not in accordance with the road conditions. Factors that affect the coordination arrangement of traffic signs is the organization of work, work methods, scheduling, and cost.Keywords: Coordination, Traffic Signs, Traffic